The impact of the green economy on the urban ecosystem of Almaty city - Sadyrova, G.A.; Sadyrov, G.A.; Sadyr, G.A.; Sadyrova, G.A. (Karagandy University of the name of acad. E.A. Buketov, 2023)
The article presents the impact of the green economy on the urbanized ecosystem of the city of Almaty. The concept of green economy is considered as sustainable development with minimal risks to the environment and the reduction of the negative impact of human economic activity on the environment, as well as the development of this direction in the country and, in particular, in the city of Almaty. A phased process of transition to a green economy is shown, the implementation of the “Zhasyl Almaty” project, where, according to the concept of transition to a green economy, according to the concept of “smart cities”, one of the main goals of the development of Almaty is to preserve natural resources, comfortable living conditions for the population and improve the quality of life in all areas of Almaty, which is the main requirement of a green economy. In recent years, the growth of new buildings in the city of Almaty has intensified the processes of anthropogenic impact on the urban flora. The existing experience of green building in the city of Almaty does not fully take into account the specific environmental conditions of various districts of the city and the level of their technogenic pollution, and the issues of the state of plantations in residential and industrial areas, the resistance of vegetation to the impact of the urban environment are ignored. Due to the increasing density of urban development with multi-storey buildings (more than 20 floors), it is becoming increasingly difficult to realize the concept of a green city of Almaty.
«Жасыл» экономиканың Алматы қаласының урбанизацияланған экожүйесіне әсері
Влияние «зеленой» экономики на урбанизированную экосистему города Алматы
Keywords: Almaty city; green economy; green spaces; city urbanization; ecosystem